Fenomenologia i kognitywizm: dwa spojrzenia na emocje w odniesieniu do świata sztuk - Zalewski, Andrzej (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2004)
The subject of this paper is the controversy between cognitivist philosophy and phenomenology concerning the nature of emotions. This article has a limited scope restricted to the domain of the aesthetic emotions usually dependent on the works of art and literature. The author raises the criticism against the cognitivist stance, this criticism based chiefly on the principles of Max Scheler's phenomenology of emotions.